Alternative way to reducing poverty and inequality in Nigeria from Islam perspective - Mohd Sadad, Mahmud; Ahmad Shukri, Yazid; Ibraheem Alani, Abdul Kareem (2020)
Poverty and inequality are global phenomena that have increased in recent times. The condition of poverty is alarming at global level as it was reported that some 57million children were out of school. Hence Ahmad and Hassan (2015) posit that half of this number was in Sub-Saharan Africa (SSA). With Nigeria as the largest nation in Africa thus it has the highest figure of these out of school children. Poverty indicates lack of income and necessary ways to achieve a standard of living. Islamic finance plays critical role in reducing the level of poverty and inequality through the profit and loss sharing among investors. Therefore, this study explores alternative way to reduce poverty and inequality from Islamic perspective in Nigeria. This would contribute to the economic development of the country. The method adopted is to review previous literature on the impacts of various Islamic financial instruments in addressing the menace of poverty and economic inequality. The study concludes that profit and loss products of Musharakah and Mudarabah, and cost based products which include Murabaha, Ijarah, Sukuk contribute to poverty reduction and promote economic activities. It thus recommends the adoption of these products in Nigeria to address the prevailing infrastructural deficit and promote economic development.